Influence of lateral loading direction on the peak shear strength of non-rectangular reinforced concrete squat walls. Issue 11 (August 2019) - Ma, Jiaxing; Li, Bing
Peak shear strength is a critical parameter in the evaluation of the seismic performance of structural walls. Different equations have been proposed to predict the peak shear strength of reinforced concrete squat walls in literature, which assume lateral loading is parallel to the web. In reality, however, seismic waves can reach structures from any direction, which necessitates the studies on the behavior of structural walls under various lateral loading directions. Unlike rectangular walls, non-rectangular walls naturally possess the capacity to resist lateral loads in both transverse and longitudinal directions. To explore the peak shear strength of such walls under different lateral loading directions, a widely used nonlinear finite element software Diana 9.4 was utilized in this article. Appropriate modeling approaches were first selected and further validated by simulating relevant experiments. Then a comprehensive parametric study was carried out to investigate the influence of lateral loading directions and other important parameters.